Graphene oxide triggers mass transfer limitations on the methanogenic activity of an anaerobic consortium with a particulate substrate. (November 2018) - Bueno-López, J. Iván; Rangel-Mendez, J. Rene; Alatriste-Mondragón, Felipe; Pérez-Rodríguez, Fátima; Hernández-Montoya, Virginia; Cervantes, Francisco J.
Abstract: Graphene oxide (GO) is an emerging nanomaterial widely used in many manufacturing applications, which is frequently discharged in many industrial effluents eventually reaching biological wastewater treatment systems (WWTS). Anaerobic WWTS are promising technologies for renewable energy production through biogas generation; however, the effects of GO on anaerobic digestion are poorly understood. Thus, it is of paramount relevance to generate more knowledge on these issues to prevent that anaerobic WWTS lose their effectiveness for the removal of pollutants and for biogas production. The aim of this work was to assess the effects of GO on the methanogenic activity of an anaerobic consortium using a particulate biopolymer (starch) and a readily fermentable soluble substrate (glucose) as electron donors. The obtained results revealed that the methanogenic activity of the anaerobic consortium supplemented with starch decreased up to 23-fold in the presence of GO compared to the control incubated in the absence of GO. In contrast, we observed a modest improvement on methane production (>10% compared to the control lacking GO) using 5 mg of GO L −1 in glucose-amended incubations. The decrease in the methanogenic activity is mainly explained by wrapping of starch granules by GO, which caused mass transfer limitation during the incubation. It is suggested that wrapping is driven by electrostatic interactions between negatively charged oxygenated groups in GO and positively charged hydroxyl groups in starch. These results imply that GO could seriously hamper the removal of particulate organic matter, such as starch, as well as methane production in anaerobic WWTS. Highlights: GO wrapped starch granules and prevented their hydrolysis. Starch granules wrapping with GO sheets was induced by electrostatic attractions. Methane yield decreased 23.3-fold due to the starch wrapping by GO. Low GO concentrations showed positive effects on methanogenesis with glucose.